Preparation method of nano-porous polyimide aerogel sandwich cylinder structure

By employing a molding method, gel curing, ethanol replacement, and supercritical drying processes, combined with multi-level shrinkage force and interference fit, a highly efficient fabrication of nanoporous polyimide aerogel sandwich cylindrical structures was achieved. This process overcomes the shortcomings of sandwich structures in terms of mechanical and thermal insulation properties, making them suitable for complex working conditions under high temperature and high pressure environments.

CN121018981APending Publication Date: 2025-11-28CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510934186.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing sandwich structures cannot simultaneously meet the requirements of mechanical performance and thermal insulation performance, especially under high temperature and high pressure environments, where interface separation and adhesive failure are prominent problems in traditional processes.

Method used

By employing a mold method and a structural co-gel method, and through gel curing, ethanol solvent replacement and supercritical drying processes, multi-stage shrinkage forces are used to achieve a tight bond between the aerogel core layer and the inner cylindrical shell. The outer cylindrical retaining sleeve is reinforced with an interference fit to enhance the overall structure.

Benefits of technology

It forms a lightweight, highly insulating, and mechanically stable composite structure, suitable for high-temperature and high-pressure environments, improves the interfacial bonding strength, avoids the defects in traditional processes, and is suitable for complex working conditions such as aerospace and industrial pipelines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121018981A_ABST
    Figure CN121018981A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano-porous polyimide aerogel sandwich cylindrical structure and the structure, and belongs to the field of aerogel sandwich structure preparation. In order to solve the problem that an existing sandwich structure is difficult to consider mechanical and heat-insulating properties, the scheme comprises the steps that an inner-layer cylindrical shell mold and an outer-layer cylindrical shell mold which are coaxially arranged are constructed, and an annular gap is formed; the preparation method comprises the following steps: preparing a polyamide acid precursor solution, performing chemical imidization, injecting the polyamide acid precursor solution into a gap, regulating interface combination through gel curing, solvent replacement and supercritical drying triple contractility, and combining interference fit assembly to form an inner-layer cylindrical shell / aerogel sandwich layer / outer-layer cylindrical retaining sleeve integrated structure. According to the method, the blank of the integrated forming technology of the aerogel sandwich cylinder structure is solved, and the prepared structure has light weight, ultralow heat conductivity and mechanical stability, is suitable for the scenes of aerospace, weaponry, industrial pipeline heat insulation and the like, and has important industrial value for improving the structural performance and energy utilization efficiency under complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of preparation of aerogel sandwich structure, in particular to a preparation method of nano-porous polyimide aerogel sandwich cylindrical structure, and especially to a composite molding process of polyimide aerogel sandwich layer and inner and outer cylindrical shell by using mold method and structure co-gel method, which is suitable for the preparation field of sandwich cylindrical structure with high requirements of light weight, mechanical properties and thermal insulation performance in aerospace, weapon equipment, industrial pipeline thermal insulation and the like. BACKGROUND

[0002] In recent years, sandwich cylindrical structure has attracted much attention in the field of composite material structure mechanics. Compared with traditional homogeneous structure, it has the advantages of significant light weight, high bearing capacity, impact resistance and energy absorption characteristics. With excellent mechanical properties, it is widely used in aerospace, underwater submarine, weapon equipment and other equipment with high impact protection performance requirements. With the expansion of application range, sandwich structure needs to have good mechanical properties and excellent thermal insulation performance under specific working conditions, which puts forward higher technical requirements. The reasonable selection of core layer material is the key to meet the requirements, and usually a lightweight material or structure with low density is used as the core layer, which plays a crucial role in the sandwich structure.

[0003] As a kind of three-dimensional porous material, aerogel has the advantages of high porosity, ultra-low density, light weight and high specific surface area due to its unique microstructure. In terms of mechanical properties, aerogel shows high strength and strong ballistic energy absorption capacity. In terms of thermal performance, it has ultra-low thermal conductivity. Based on these excellent properties, aerogel shows broad application prospects in military facilities, firefighting tools, energy storage devices, anti-seismic pressure relief, sound insulation and absorption, and aerospace and other fields.

[0004] Therefore, it is of great industrial application value to develop an integrated forming preparation technology of nano-porous polyimide aerogel sandwich composite cylindrical structure, and to prepare a polyimide aerogel sandwich composite cylindrical structure with good mechanical and thermal properties. SUMMARY

[0005] In view of the above-mentioned deficiencies of the prior art, the present application aims to provide a preparation method of nano-porous polyimide aerogel sandwich cylindrical structure, which solves the problem that the existing sandwich structure cannot simultaneously meet the requirements of mechanical properties and thermal insulation performance, and prepares a composite structure with light weight, high thermal insulation and mechanical stability.

[0006] To achieve the above-mentioned application purposes, the technical solutions adopted are as follows:

[0007] The application discloses a preparation method of a nanometer porous polyimide aerogel sandwiched cylindrical structure, and comprises the following steps: S1, a mold is constructed, the mold comprises an inner layer cylindrical shell and an outer layer cylindrical shell arranged coaxially, and an annular gap is formed between the inner layer and the outer layer; S2, a polyamide acid precursor solution is prepared and subjected to chemical imidization; S3, the polyamide acid precursor solution which has not been solidified after chemical imidization is injected into the annular gap between the inner layer and the outer layer of the mold, and the gel sandwiched layer is formed after solidification, and the gel sandwiched layer is preliminarily and tightly combined with the inner layer cylindrical shell by means of the shrinkage force in the gel solidification process to form a combined body, but is separated from the outer layer cylindrical shell; S4, the combined body obtained in the step S3 is immersed in ethanol for solvent replacement, so that the preliminary tightness between the wet gel and the inner layer cylindrical shell is further enhanced by means of the shrinkage force in the solvent replacement process; S5, the combined body treated in the step S4 is subjected to supercritical drying, so that the gel sandwiched layer is further tightly combined with the inner layer cylindrical shell by means of the gel shrinkage deformation caused by the supercritical drying; and S6, the outer layer cylindrical retaining sleeve is arranged on the gel sandwiched layer based on the interference fit mode, so as to form the nanometer porous polyimide aerogel sandwiched cylindrical structure.

[0008] The preparation method of the application realizes the integrated forming of the nanometer porous polyimide aerogel sandwiched cylindrical structure by an innovative process. The mold method and the structure co-gel method are adopted, the annular gap is formed by the inner layer cylindrical shell and the outer layer cylindrical shell mold, the wet gel is preliminarily combined with the inner layer cylindrical shell and separated from the outer layer cylindrical shell by means of the shrinkage force in the gel solidification process, the defects of interface separation in the traditional process are avoided, the integrated preparation of the cylindrical aerogel sandwiched structure is realized for the first time, and the technical blank in the field is filled.

[0009] In the aspect of improving the bonding strength, the preliminary tightness effect is enhanced by multi-stage shrinkage force: the first shrinkage after the gel solidification realizes the preliminary combination, the second shrinkage in the ethanol solvent replacement process further enhances the mechanical occlusion force, and the third shrinkage in the supercritical drying promotes the molecular level close contact between the aerogel and the inner layer cylindrical shell. The multi-stage shrinkage effect significantly reduces the initial defects of the structure, improves the interface bonding strength, and makes the aerogel sandwiched layer and the inner layer cylindrical shell form a stable whole, avoiding the problems of adhesive failure or mechanical connection loosening in the traditional assembly process.

[0010] The supercritical drying process enhances the bonding force while retaining the nanometer porous structure of the aerogel. The structure has high porosity and ultra-low thermal conductivity, so that the prepared sandwiched cylindrical structure performs excellently in the heat insulation field, can effectively reduce the heat loss of high-temperature and high-pressure pipelines, for example, in the scenes of oil and natural gas transportation, chemical raw material pipeline transportation and the like, can maintain the stability of medium temperature and reduce the energy waste and pipeline corrosion risk caused by heat loss, and the efficiency is significantly improved compared with traditional heat insulation materials.

[0011] The sandwiched cylinder structure formed finally has the advantages of light weight, high bearing capacity and impact resistance, and has application advantages in fields such as aerospace and weapon equipment which have high requirements on mechanical properties. Meanwhile, the excellent thermal stability and heat insulation property meet the long-term use requirement in high-temperature environment, and provide a new path for multifunctional design of composite structures.

[0012] In the present application, in step S3, after chemical imidization, the uncured polyamic acid precursor solution is injected into the annular gap of the mold and solidified, and the formed gel is called "wet gel" because it contains a large amount of solvent (such as N-methyl pyrrolidone, etc.). At this time, the wet gel is preliminarily combined with the inner layer cylindrical shell through the solidification shrinkage force, but is separated from the outer layer cylindrical shell. In step S4, the combination of the wet gel and the inner layer cylindrical shell is immersed in ethanol for solvent replacement, and the ethanol gradually replaces the original solvent in the pores of the wet gel. This process is accompanied by gel shrinkage, which further enhances the pre-tightening force of the gel with the inner layer cylindrical shell, but the gel still contains liquid solvent and is still in a wet gel state. In step S5, the supercritical drying method is used to place the combination after solvent replacement in a supercritical drying environment, so that the ethanol solvent in the pores of the wet gel is taken away, and the wet gel is converted into aerogel. The gel shrinkage deformation caused by drying further makes it tightly combined with the inner layer cylindrical shell, forming an integrated composite structure.

[0013] Further, the polyamic acid precursor solution is prepared from solid polyamic acid and a solvent capable of dissolving polyamic acid.

[0014] Further, the polyamic acid solution is prepared by polymerization of a dianhydride monomer and a diamine monomer; wherein the dianhydride monomer is selected from any one or more of pyromellitic dianhydride, biphenyl tetracarboxylic dianhydride, benzophenone tetracarboxylic dianhydride, and diphenyl ether tetracarboxylic dianhydride; and the diamine monomer is selected from any one or more of diaminodiphenyl ether, 4,4'-diphenyl ether diamine, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(4-aminophenyl)-5-aminobenzimidazole, m-phenylenediamine, and 4,4'-diaminobenzanilide.

[0015] In the present application, the polyamic acid precursor solution can be prepared in two ways: one is prepared from solid polyamic acid and a solvent capable of dissolving polyamic acid, and the other is prepared by polymerization of a dianhydride monomer (selected from any one or more of pyromellitic dianhydride, biphenyl tetracarboxylic dianhydride, etc.) and a diamine monomer (selected from any one or more of diaminodiphenyl ether, 4,4'-diphenyl ether diamine, etc.). This raw material selection and preparation method has the advantages of easy availability of raw materials and flexible process, and can select appropriate monomer combination and preparation method according to different application scenarios and performance requirements, to provide stable precursor for subsequent sol-gel method and chemical imidization reaction, and to ensure the feasibility and adaptability of the preparation process of the nano-porous polyimide aerogel sandwiched cylinder structure.

[0016] Further, the inner cylindrical shell is made of a structural target surface layer material, and the outer cylindrical shell is made of a material with inactive surface chemical properties.

[0017] In the present application, the inner cylindrical shell is made of a structural target surface layer material, which can directly provide the prepared sandwich cylindrical structure with the mechanical properties of the target surface layer, avoiding subsequent secondary processing loss; the outer cylindrical shell is made of a material with inactive surface chemical properties, which can ensure that the gel automatically separates from the outer cylindrical shell after solidification due to its low adhesion, thereby reducing the demolding resistance and avoiding damage to the gel sandwich layer, and also eliminating the need for additional release agents, ensuring the structural integrity, simplifying the process steps, and improving the preparation efficiency and structural reliability.

[0018] Further, the inner cylindrical shell is made of a structural target surface layer material, and the outer cylindrical shell is made of a material with inactive surface chemical properties.

[0019] Further, in step S4, the combination is immersed in ethanol at room temperature, and the ethanol is replaced every 10-14 hours for immersion for no less than 48 hours.

[0020] In the present application, the combination is immersed in ethanol at room temperature for no less than 48 hours, and the ethanol is replaced every 10-14 hours, which can ensure that the original solvent in the wet gel pores is fully replaced by ethanol, and the solvent replacement efficiency and purity are maintained by periodically replacing the ethanol; during this process, the gel uniformly shrinks and generates secondary shrinkage force, further enhancing the pre-tightening force between the wet gel and the inner cylindrical shell, optimizing the interfacial bonding strength, avoiding structural defects caused by residual solvents or insufficient replacement, and ensuring the mechanical stability and preparation reliability of the nano-porous polyimide aerogel sandwich cylindrical structure.

[0021] Further, in step S5, the combination treated in step S4 is subjected to supercritical drying in a supercritical drying oven, the drying oven pressure is maintained at 8-12 MPa, the temperature is set to 30-50℃, and carbon dioxide is used to flush the supercritical drying oven to remove the liquid in the gel pores, thereby completing the supercritical drying.

[0022] In the present application, the combination after step S4 is placed in a supercritical drying oven, and the liquid in the gel pores is flushed away by carbon dioxide at a pressure of 8-12 MPa and a temperature of 30-50 DEG C. Under these conditions, the carbon dioxide is in a supercritical state, combining the high density of a liquid with the high diffusion coefficient of a gas, which can efficiently penetrate into the interior of the wet gel pores. The low surface tension characteristic avoids the damage to the nano-porous structure caused by the surface tension generated by solvent evaporation in traditional drying, ensuring the complete retention of the aerogel pores. At the same time, the shrinkage of the gel during supercritical drying further strengthens the close combination with the inner cylindrical shell, improving the interfacial bonding strength, and finally obtaining a nano-porous polyimide aerogel sandwich composite cylindrical structure with stable structure and excellent mechanical properties.

[0023] Further, in step S6, the inner diameter size of the outer cylindrical retaining sleeve is determined based on the outer diameter size before supercritical drying of the gel sandwich layer and the linear shrinkage rate, and the inner diameter size is equal to or less than the outer diameter size after drying of the gel sandwich layer, so that the outer cylindrical retaining sleeve and the gel sandwich layer form an interference fit.

[0024] Further, the linear shrinkage rate is set as the ratio of the difference between the outer diameter before drying and the outer diameter after drying of the gel sandwich layer to the outer diameter before drying.

[0025] In the present application, the inner diameter size of the outer cylindrical retaining sleeve needs to be determined based on the outer diameter size before supercritical drying of the gel sandwich layer and the linear shrinkage rate. The calculation formula of the linear shrinkage rate is as follows:

[0026]

[0027] wherein η is the linear shrinkage rate, R1 is the outer diameter before drying of the gel sandwich layer, and R2 is the outer diameter after drying. The formula calculates the ratio of the difference between the outer diameters before and after drying to the outer diameter before drying and expresses it as a percentage, providing an accurate quantitative basis for the selection of the outer cylindrical retaining sleeve.

[0028] Through the above calculation, the inner diameter size of the outer cylindrical retaining sleeve is equal to or less than the outer diameter size after drying of the gel sandwich layer, thereby forming an interference fit. When assembled, the outer cylindrical retaining sleeve elastically deforms due to the small size difference, tightly contacts the surface of the aerogel sandwich layer, and realizes glue-free connection by relying on the friction force generated by elastic deformation.

[0029] This design has many advantages: first, it avoids damage to the nano-porous structure of aerogel by adhesive, maintaining its thermal insulation and mechanical properties; second, it enhances the overall mechanical stability of the structure through close contact, effectively transfers stress, and prevents relative displacement or loosening; third, it simplifies the assembly process and reduces production costs, and is suitable for scenarios such as aerospace and industrial pipelines that require high structural reliability, ensuring the integrated performance of the sandwich cylindrical structure in complex environments.

[0030] The application also discloses a nanoporous polyimide aerogel sandwiched cylindrical structure prepared according to the preparation method of the nanoporous polyimide aerogel sandwiched cylindrical structure; the nanoporous polyimide aerogel sandwiched cylindrical structure comprises an inner layer cylindrical shell, a gel sandwiched layer arranged on the outer side of the inner layer cylindrical shell, and an outer layer cylindrical retaining sleeve arranged on the outer side of the gel sandwiched layer in an interference fit. The structure has multiple advantages: the inner layer cylindrical shell provides structural support, the gel sandwiched layer realizes ultralow thermal conductivity relying on the nanoporous structure, and the outer layer cylindrical retaining sleeve enhances the overall reliability through interference fit, forming a composite structure with light weight, high thermal insulation and mechanical stability. The structure is suitable for aerospace, weapon equipment, energy and chemical industry, industrial pipeline and other fields, and can meet the long-term thermal insulation demand under high temperature environment and the scene with high requirements for impact protection and structural load bearing.

[0031] The application has the following beneficial effects compared with the prior art:

[0032] The application realizes the pre-tightening combination of the polyimide aerogel sandwiched layer and the inner layer cylindrical shell and the automatic separation of the polyimide aerogel sandwiched layer and the outer layer cylindrical shell through coaxial arrangement and annular gap design of the mold; the synergistic effect of chemical imidization, ethanol solvent replacement and supercritical drying process is utilized to control the interface bonding strength through multi-stage shrinkage force, so that the structure collapse caused by traditional drying is avoided and the nanoporous characteristics are retained; finally, the outer layer cylindrical retaining sleeve is arranged in an interference fit to form an integrated composite structure with light weight, high thermal insulation (ultralow thermal conductivity) and mechanical stability, thereby solving the problem that the existing sandwiched structure is difficult to simultaneously meet the high strength load bearing and high efficiency thermal insulation demand, and widening the application scene of the structure in aerospace, weapon preparation, high temperature industrial pipeline and other complex working conditions.

[0033] The nanoporous polyimide aerogel sandwiched cylindrical structure preparation method of the application will be disclosed in detail below with reference to the embodiments shown in the drawings. BRIEF DESCRIPTION OF DRAWINGS

[0034] Figure 1 The figure is a flow step diagram of the nanoporous polyimide aerogel sandwiched cylindrical structure preparation method of the application;

[0035] Figure 2 The figure is a preparation schematic diagram of the mold method and the structure co-gel method in step S3 of the flow;

[0036] Figure 3 The figure is a 6061T6 aluminum alloy / polyimide aerogel / 6061T6 aluminum alloy sandwiched cylindrical structure prepared in Example 1 of the application;

[0037] Figure 4 The figure is a 3K carbon fiber tube / polyimide aerogel composite sandwiched cylindrical structure prepared in Example 2 of the application. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0039] In the field of composite material structure mechanics, the sandwich cylindrical structure is widely used in the fields of aerospace, weapon equipment, etc., but it needs to have excellent mechanical and thermal insulation properties under specific working conditions, and the selection of the core material becomes the key. Aerogel has advantages of high porosity, ultra-low density, low thermal conductivity and high strength, but lacks an integrated forming preparation process suitable for the sandwich cylindrical structure of aerogel, which limits its engineering application. Therefore, the present application provides a preparation method of a nano-porous polyimide aerogel sandwich cylindrical structure to solve the above technical bottleneck.

[0040] As shown in Figure 1 With Figure 2 The present application discloses a preparation method of a nano-porous polyimide aerogel sandwich cylindrical structure, comprising the following steps: S1, constructing a mold, the mold comprising an inner cylindrical shell and an outer cylindrical shell arranged coaxially, and having an annular gap between the inner and outer layers; S2, preparing a polyamide acid precursor solution and causing it to undergo chemical imidization; S3, injecting the polyamide acid precursor solution that has not yet solidified after chemical imidization into the annular gap between the inner and outer layers of the mold, waiting for the gel sandwich layer to form, and using the shrinkage force during gel solidification to make the gel sandwich layer preliminarily pre-tighten and combine with the inner cylindrical shell to form a combined body, but separate from the outer cylindrical shell; S4, immersing the combined body obtained in step S3 in ethanol for solvent replacement, so as to further enhance the pre-tightening force between the wet gel and the inner cylindrical shell by means of the shrinkage force during solvent replacement; S5, supercritically drying the combined body treated in step S4, so as to make the gel sandwich layer further tightly combine with the inner cylindrical shell by means of the gel shrinkage deformation caused by supercritical drying; and S6, setting an outer cylindrical retaining sleeve on the gel sandwich layer based on interference fit, to form a nano-porous polyimide aerogel sandwich cylindrical structure.

[0041] Based on the above disclosed steps, the present application first realizes the integrated forming of the nano-porous polyimide aerogel sandwich cylindrical structure. The mold method and the structure co-gel method are adopted to form an annular gap with the inner cylindrical shell and the outer cylindrical shell mold, and the shrinkage force during gel solidification is used to preliminarily combine the wet gel with the inner cylindrical shell and separate it from the outer cylindrical shell, avoiding the defects of interface separation in the traditional process, and first realizing the integrated preparation of the cylindrical aerogel sandwich structure, filling the technical gap in this field.

[0042] In terms of bond strength improvement, the pre-tightening effect is enhanced by multi-stage shrinkage force: the first shrinkage after gel solidification realizes preliminary bonding, the second shrinkage during ethanol solvent replacement further enhances the mechanical bite force, and the third shrinkage during supercritical drying promotes the molecular-level close contact between aerogel and inner cylindrical shell. This multi-stage shrinkage effect significantly reduces the initial defects of the structure, improves the interface bonding strength, and makes the aerogel sandwich layer and the inner cylindrical shell form a stable whole, avoiding the problems of adhesive failure or mechanical connection loosening in traditional assembly process.

[0043] The supercritical drying process not only enhances the bonding force, but also preserves the nano-porous structure of the aerogel. This structure has high porosity and ultra-low thermal conductivity, making the prepared sandwich cylindrical structure perform excellently in the field of thermal insulation. It can effectively reduce the heat loss of high-temperature and high-pressure pipelines, such as petroleum and natural gas transportation, chemical raw material pipeline transportation, etc., maintaining the stability of medium temperature and reducing energy waste and pipeline corrosion risk caused by heat loss, significantly improving the efficiency compared with traditional thermal insulation materials.

[0044] The final sandwiched cylindrical structure has the advantages of lightweight, high bearing capacity and impact resistance, and has application advantages in fields such as aerospace and weapon equipment that require high mechanical properties. At the same time, its excellent thermal stability and thermal insulation meet the long-term use requirements in high-temperature environments, providing a new path for the multifunctional design of composite structures.

[0045] In one specific embodiment, the following operations are taken when assembling the mold in step S1: First, vaseline is applied to the bottom surface of the inner and outer cylindrical shells to prevent solution leakage; then the inner and outer cylindrical shells are fixed and bonded on the glass plate in a concentric circular structure to ensure uniform coaxial annular gap. The above operations can ensure the uniformity of the gel layer thickness and the precision of the structure size, and the use of common materials reduces the cost and difficulty of mold preparation.

[0046] In the embodiment of the present application, the polyamide acid precursor solution in step S2 is prepared by two methods: using solid polyamide acid and a solvent that can dissolve polyamide acid; or using dianhydride monomers and diamine monomers to polymerize in an organic solvent, wherein the dianhydride monomers are selected from any one or more of pyromellitic dianhydride, biphenyl tetracarboxylic dianhydride, benzophenone tetracarboxylic dianhydride, and diphenyl ether tetracarboxylic dianhydride; the diamine monomers are selected from any one or more of 4,4'-oxydianiline, 4,4'-oxydianiline, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(4-aminophenyl)-5-aminobenzimidazole, m-phenylenediamine, and 4,4'-diaminobenzanilide.

[0047] Specifically, one is to prepare a solution by dissolving the polyamic acid in dimethyl sulfoxide, N-methyl pyrrolidone or other suitable organic solvents, and the mass fraction of the polyamic acid in the solution is generally 5% to 20%, and the concentration can be adjusted according to specific requirements; the other is to prepare the polyamic acid by polymerization of a dianhydride monomer and a diamine monomer in an organic solvent, wherein the dianhydride monomer can be selected from one or more of pyromellitic dianhydride, biphenyl tetracarboxylic dianhydride, benzophenone tetracarboxylic dianhydride, and diphenyl ether tetracarboxylic dianhydride, and the diamine monomer can be selected from one or more of 4,4'-oxydianiline, 4,4'-oxydianiline, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(4-aminophenyl)-5-aminobenzimidazole, m-phenylenediamine, and 4,4'-diaminobenzanilide, and other related monomers in the prior art can also be used, and the organic solvent is selected from dimethyl sulfoxide, N-methyl pyrrolidone, dimethylacetamide and other types having good solubility and thermal stability, which can provide a suitable reaction environment for polymerization, and the polymerization process parameters (monomer amount, solvent, polymerization temperature, polymerization time, etc.) can refer to the prior art, and the present application does not make specific limitations thereon to adapt to different scene requirements.

[0048] In the present application, the chemical imidization of the polyamic acid precursor solution is a key step for preparing polyimide, and the principle is to promote imidization by reacting a dehydrating agent with the carboxyl groups in the polyamic acid, while stabilizing the reaction process by a catalyst to accelerate dehydration and improve imidization efficiency.

[0049] In a specific embodiment, the commonly used dehydrating agent includes acetic anhydride, propionic anhydride, etc., and the catalyst includes tertiary amine, isoquinoline, pyridine, etc., and since the reagents such as pyridine have a pungent odor, this step needs to be operated in a fume hood, specifically, the dehydrating agent and the catalyst are slowly added to the polyamic acid solution under stirring, wherein the amount of the dehydrating agent is generally 0.8 to 1.2 times the molar amount of the carboxyl groups in the polyamic acid, and the amount of the catalyst is generally 10% to 20% of the molar amount of the dehydrating agent, and the reaction temperature and time can be optimized according to the molecular structure of the polyamic acid and the performance requirements of the target product, and the general reagents, amounts and operation steps can refer to the prior art, and the present application does not make specific limitations thereon.

[0050] In a preferred embodiment of the present application, the inner cylindrical shell is made of the structural target surface layer material, and the outer cylindrical shell is made of a material with inactive surface chemical properties. Among them, the use of the structural target surface layer material for the inner layer can make the prepared sandwiched cylindrical structure directly have the mechanical properties of the target surface layer, avoiding the subsequent secondary processing loss; the use of the material with inactive surface chemical properties for the outer layer can ensure that the gel is automatically separated from the outer cylindrical shell after solidification, which not only can reduce the demolding resistance and avoid damaging the gel sandwiched layer, but also does not need to use additional release agent, thereby ensuring the structural integrity, and at the same time simplifying the process steps, improving the preparation efficiency and the structural reliability.

[0051] In one specific embodiment, the inner cylindrical shell can be made of metal or composite metal tube, carbon fiber tube; the outer cylindrical shell is made of at least one of glass, polypropylene, polytetrafluoroethylene, epoxy resin.

[0052] In one preferred embodiment of the present application, the curing time in step S3 is 4-5 hours, which can ensure that the polyamide acid precursor solution is fully chemically cross-linked to form a gel sandwich layer, while avoiding insufficient curing time leading to insufficient gel strength or excessive time causing excessive shrinkage. By controlling the curing time within a reasonable range, both the preliminary pre-tightening combination of the gel sandwich layer and the inner cylindrical shell through the curing shrinkage force and the smooth separation from the outer cylindrical shell can be achieved, laying a foundation for subsequent solvent replacement and supercritical drying process, and ensuring the forming quality and interfacial bonding performance of the nano-porous polyimide aerogel sandwich cylindrical structure.

[0053] In one preferred embodiment of the present application, step S4 is specifically: immersing the combination in ethanol at room temperature, replacing the ethanol every 10-14 hours (for example, 12 hours), and immersing for not less than 48 hours. Through this operation, the original solvent in the wet gel pores can be fully replaced by ethanol, and the efficiency and purity of solvent replacement can be maintained by periodically replacing the ethanol; in this process, the gel uniformly shrinks and generates secondary shrinkage force, further enhancing the pre-tightening force between the wet gel and the inner cylindrical shell, optimizing the interfacial bonding strength, avoiding structural defects caused by residual or insufficient solvent replacement, and ensuring the mechanical stability and preparation reliability of the nano-porous polyimide aerogel sandwich cylindrical structure.

[0054] In one preferred embodiment of the present application, step S5 is specifically: supercritical drying the combination treated in step S4 in a supercritical drying oven, maintaining the pressure of the drying oven at 8-12 MPa (for example, 10 MPa), setting the temperature to 30-50℃ (for example, 40℃), and using carbon dioxide flushing to remove the liquid in the gel pores, completing the supercritical drying. Under these conditions, carbon dioxide is in a supercritical state, combining the characteristics of high density of liquid and high diffusion coefficient of gas, can efficiently penetrate into the interior of the wet gel pores, avoid the damage to the nano-porous structure caused by surface tension generated in traditional drying due to solvent evaporation, ensure the complete retention of the aerogel pores; at the same time, the gel shrinkage deformation during supercritical drying further strengthens the close combination with the inner cylindrical shell, improves the interfacial bonding strength, and finally obtains a nano-porous polyimide aerogel sandwich composite cylindrical structure with stable structure and excellent mechanical properties.

[0055] In a preferred embodiment of the present application, in step S6, the outer diameter size before supercritical drying of the gel sandwich layer and the linear shrinkage rate are used to determine the inner diameter size of the outer layer cylindrical retaining sleeve, and the inner diameter size is equal to or smaller than the outer diameter size of the gel sandwich layer after drying, so that the outer layer cylindrical retaining sleeve and the gel sandwich layer form an interference fit. In this embodiment, the linear shrinkage rate is the ratio of the difference between the outer diameter before drying and the outer diameter after drying to the outer diameter before drying, and the calculation formula is as follows:

[0056]

[0057] where η is the linear shrinkage rate, R1 is the outer diameter before drying of the gel sandwich layer, and R2 is the outer diameter after drying. The formula calculates the ratio of the difference between the outer diameters before and after drying to the outer diameter before drying and expresses it as a percentage, providing an accurate quantitative basis for the selection of the outer layer cylindrical retaining sleeve.

[0058] Through the above calculation, the inner diameter size of the outer layer cylindrical retaining sleeve is equal to or smaller than the outer diameter size of the gel sandwich layer after drying, thereby forming an interference fit. When assembled, the outer layer cylindrical retaining sleeve elastically deforms due to the slight size difference, tightly contacts the surface of the aerogel sandwich layer, and realizes glue-free connection by relying on the friction force generated by elastic deformation.

[0059] This design has many advantages: first, it avoids damage to the aerogel nanoporous structure caused by adhesives, maintaining its thermal and mechanical properties; second, it enhances the overall mechanical stability of the structure through tight contact, effectively transfers stress, and prevents relative displacement or loosening; third, it simplifies the assembly process and reduces production costs, making it suitable for scenarios with high requirements for structural reliability such as aerospace, industrial pipelines, etc., ensuring the integrated performance of the sandwich cylindrical structure in complex environments.

[0060] The present application also discloses a nanoporous polyimide aerogel sandwich cylindrical structure prepared according to the disclosed preparation method. The nanoporous polyimide aerogel sandwich cylindrical structure comprises an inner layer cylindrical shell, a gel sandwich layer tightly arranged on the outer side of the inner layer cylindrical shell, and an outer layer cylindrical retaining sleeve in interference fit with the outer side of the gel sandwich layer. This structure has multiple advantages: the inner layer cylindrical shell provides structural support, the gel sandwich layer relies on the nanoporous structure to achieve ultra-low thermal conductivity, and the outer layer cylindrical retaining sleeve enhances the overall reliability through interference fit, forming a lightweight, high-thermal-insulation, and mechanically stable composite structure. It is suitable for aerospace, weapon equipment, energy and chemical industry, industrial pipeline, etc., and can meet the long-term thermal insulation requirements in high-temperature environments and the requirements of high-impact protection and structural load in certain scenarios.

[0061] These performance advantages make it unique in the field of thermal insulation, thereby opening up broad prospects for the widespread application of sandwich composite cylindrical structures.

[0062] The nanometer porous polyimide aerogel sandwiched cylindrical structure prepared by the present application has low thermal conductivity and high porosity, and has significant application advantages in the field of thermal insulation, providing a broad prospect for the wide application of sandwiched composite cylindrical structures.

[0063] In industrial production, there are many scenarios that require long-distance pipeline transportation of high-temperature and high-pressure gas or liquid, such as long-distance transportation of oil and natural gas, pipeline transportation of chemical raw materials, and distribution of high-temperature steam, etc. In these application scenarios, traditional thermal insulation materials often fail to meet the demand for efficient thermal insulation, resulting in a large amount of heat loss along the pipeline, which not only reduces energy utilization efficiency, but also may cause thermal pollution to the environment around the pipeline. Taking the transportation of oil and natural gas pipelines as an example, natural gas usually needs to be transported over a long distance after being extracted before reaching the end user. During the transportation process, the temperature of the natural gas will gradually decrease due to environmental factors and heat dissipation of the pipeline, which may cause the condensation of water in the natural gas, thereby causing pipeline corrosion and blockage, etc. In addition, the heat loss will also reduce the pressure of the natural gas in the pipeline, increasing the energy consumption of transportation. Using the nanometer porous polyimide aerogel sandwiched cylindrical structure as the pipeline thermal insulation layer can effectively reduce the heat transfer rate. Due to its low thermal conductivity, this structure can significantly reduce the heat exchange between the inside and outside of the pipeline, thereby maintaining the temperature stability of the medium in the pipeline and improving the thermal insulation effect. At the same time, the high-porosity aerogel structure can further enhance the thermal insulation performance and reduce the heat loss through heat conduction and heat convection.

[0064] In the chemical industry, many chemical raw materials need to be transported through pipelines under high temperature and high pressure conditions. For example, in the ammonia synthesis industry, the mixed gas of hydrogen and nitrogen needs to be transported through pipelines under high temperature and high pressure to the reactor. In such processes, the thermal insulation performance of the pipeline is crucial. If a large amount of heat is lost, it will not only cause the temperature of the reactants to drop, affecting the reaction efficiency, but also increase the energy consumption of the heating equipment. The thermal insulation layer of the nanometer porous polyimide aerogel sandwiched cylindrical structure can effectively reduce the heat loss of the pipeline and ensure the stability of the temperature and pressure of the medium in the pipeline, thereby improving the efficiency and safety of chemical production.

[0065] In the application scenarios of high-temperature steam pipelines, such as in power plants or central heating systems, high-temperature steam is transported through pipelines to various user ends. Traditional thermal insulation materials may have problems such as reduced thermal insulation performance and material aging in high-temperature environments. However, the nanometer porous polyimide aerogel sandwiched cylindrical structure has excellent thermal stability and can maintain good thermal insulation performance under high-temperature conditions for a long time, reducing the loss of steam heat, thereby improving the utilization efficiency of steam and reducing energy consumption. By using this structure, not only can the goal of energy saving and emission reduction be achieved, but also the service life of the pipeline can be effectively prolonged and the maintenance cost can be reduced.

[0066] In summary, the nanoporous polyimide aerogel sandwich cylindrical structure, with its low thermal conductivity and high porosity, has significant application value in the field of thermal insulation for long-distance pipeline transportation of high-temperature and high-pressure gases and liquids. It can effectively reduce heat transfer, improve thermal insulation effect, and thus achieve efficient energy utilization and energy conservation and emission reduction, providing important technical support for the development of related industrial fields.

[0067] like Figure 3 and Figure 4 As shown, this invention utilizes an innovative process to fabricate polyimide aerogel sandwich cylindrical structures with different surface layer materials. The following detailed examples illustrate the preparation method and process applicability of this structure within a metal (6061T6 aluminum alloy) and composite material (3K carbon fiber tube) system.

[0068] Example 1: Fabrication of a sandwich-core cylindrical structure of 6061T6 aluminum alloy / polyimide aerogel / 6061T6 aluminum alloy

[0069] Step 1: Mold Preparation

[0070] A mold is prepared by coaxially arranging an inner cylindrical shell and an outer cylindrical shell, with an annular gap of 10 mm thickness between them. The inner cylindrical shell is made of 6061T6 aluminum alloy with an inner diameter of 30 mm and a wall thickness of 1 mm, while the outer cylindrical shell is made of polytetrafluoroethylene (with inactive surface chemicals, facilitating demolding).

[0071] Step 2: Preparation of polyamic acid precursor solution and chemical imidization

[0072] 4,4'-Diamino-3,3'-dimethylbiphenyl monomer and pyromellitic acid monomer were dissolved in N-methylpyrrolidone (NMP) and polymerized to obtain a 10% (w / w) polyamic acid solution. Subsequently, propionic anhydride (dehydrating agent) and pyridine (catalyst) were added to the solution in a molar ratio of 4:4:1, and the mixture was stirred continuously for 5 minutes until fully mixed to promote the imidization reaction and generate the polyimide precursor.

[0073] Step 3: Gel curing and initial demolding

[0074] The mixed solution obtained in step 2 is slowly poured into the 10mm thick annular gap of the mold in step 1 and left to stand for 4 hours. The gel shrinks and deforms due to the chemical imidization reaction, resulting in a wet gel. At this time, the wet gel is tightly bonded to the inner 6061T6 aluminum alloy due to shrinkage, while the outer polytetrafluoroethylene cylindrical shell can be easily detached due to its inactive surface chemical properties, thus retaining the integrated structure of "6061T6 aluminum alloy-wet gel".

[0075] Step 4: Solvent replacement (ethanol replacement)

[0076] The "6061 T6 aluminum alloy-wet gel" was fully immersed in ethanol for 48 hours solvent replacement to replace the NMP solvent in the wet gel pores with ethanol gradually. During the replacement process, the ethanol was replaced every 12 hours to ensure sufficient replacement and maintain solvent purity, while promoting further shrinkage of the wet gel and enhancing the bonding force with the inner aluminum alloy by using the ethanol environment.

[0077] Step 5: Supercritical drying

[0078] The sample after complete solvent replacement was removed and measured for the inner and outer diameters and height of the wet gel layer. It was then placed in a supercritical drying oven for 6 hours of carbon dioxide supercritical drying at a pressure of 10 MPa and a temperature of 40°C. Supercritical carbon dioxide penetrated into the interior of the wet gel pores, gradually replacing ethanol and carrying out the solvent, while avoiding pore collapse and preserving the nanoporous structure using the low surface tension characteristics. During the drying process, the wet gel further shrunk to form a more intimate physical fit with the inner aluminum alloy, resulting in an integrally formed nanoporous polyimide aerogel with its inner aluminum alloy.

[0079] Step 6: Shrinkage calculation and finished product assembly

[0080] By measuring the radial and circumferential dimensions of the gel before and after drying, the radial linear shrinkage was calculated to be 13.68%, and the circumferential linear shrinkage was calculated to be 15.03%. According to the shrinkage data, the size of the outer cylindrical shell was pre-calculated, and an outer 6061 T6 aluminum alloy cylindrical shell with a size matching the outer dimensions of the dried aerogel and inner aluminum alloy was selected and fitted on the outermost side through interference fit (the size difference was designed based on the shrinkage). The pre-tightening force and friction force generated by the elastic deformation of the material made the outer aluminum alloy tightly fit the internal structure, forming a "6061 T6 aluminum alloy / polyimide aerogel / 6061 T6 aluminum alloy" sandwiched cylindrical structure without the need for additional gluing or mechanical fixation, ensuring the overall mechanical properties and stability.

[0081] Example 2: Preparation of 3K carbon fiber tube / polyimide aerogel composite sandwiched cylindrical structure

[0082] Step 1: Mold preparation

[0083] A mold was prepared with an inner cylindrical shell and an outer cylindrical shell coaxially arranged, forming an annular gap between them. The inner cylindrical shell was a 3K carbon fiber tube with an inner diameter of 29 mm, a wall thickness of 1 mm, and a fiber direction of 45°, and the outer cylindrical shell was made of polytetrafluoroethylene (PTFE) (with inactive surface chemical properties for easy demolding).

[0084] Step 2: Preparation of polyamide acid precursor solution and chemical imidization

[0085] A 5% by mass polyamic acid solution was prepared by polymerization of 4,4'-diamino-3,3'-dimethylbiphenyl monomers and pyromellitic acid monomers in N-methyl pyrrolidone (NMP). Subsequently, propionic anhydride (dehydrating agent) and pyridine (catalyst) were added to the solution in a 4:4:1 molar ratio, and the mixture was stirred for 5 minutes to promote imidization to form a polyimide precursor.

[0086] Step 3: Gel solidification and preliminary demolding

[0087] The mixed solution prepared in Step 2 was slowly poured into the 10 mm thick annular gap of the mold of Step 1, and left to stand for 5 hours to induce gel shrinkage deformation by chemical imidization, obtaining a wet gel. At this time, the wet gel was tightly combined with the inner layer of 3K carbon fiber tubes due to shrinkage, and the outer layer of polytetrafluoroethylene cylindrical shells could be easily removed due to chemical inertness, leaving an integrated structure of "3K carbon fiber tube-wet gel".

[0088] Step 4: Solvent replacement (ethanol replacement)

[0089] The "3K carbon fiber tube-wet gel" was completely immersed in ethanol for 72 hours of solvent replacement, gradually replacing the NMP solvent in the pores of the wet gel with ethanol. During the replacement process, the ethanol was replaced every 12 hours to ensure sufficient replacement and maintain the purity of the solvent, while the ethanol environment was used to promote further shrinkage of the wet gel and enhance the bonding force with the inner layer of 3K carbon fiber tubes.

[0090] Step 5: Supercritical drying

[0091] The sample after complete solvent replacement was removed, and the inner and outer diameters and height of the wet gel layer were measured. Then, it was placed in a supercritical drying oven, and supercritical carbon dioxide drying was performed at a pressure of 10 MPa and a temperature of 40°C for 6 hours. The supercritical carbon dioxide penetrated into the pores of the wet gel, gradually replacing the ethanol and carrying out the solvent, while the low surface tension characteristics were used to avoid pore collapse and maintain the nano-porous structure. During the drying process, the wet gel further shrunk and formed a tighter physical fit with the inner layer of 3K carbon fiber tubes, obtaining an integrated nano-porous polyimide aerogel with its inner layer of 3K carbon fiber tubes.

[0092] Step 6: Shrinkage calculation and finished product assembly

[0093] The radial linear shrinkage rate is 7.62% and the circumferential linear shrinkage rate is 9.25% by measuring the radial and circumferential sizes of the gel before and after drying. The size of the outer cylindrical shell is calculated in advance according to the shrinkage rate data, and the outer 3K carbon fiber tube cylindrical shell matching the size of the outer surface of the dried aerogel and the inner 3K carbon fiber tube is sleeved on the outermost side through interference fit (the size difference is designed based on the shrinkage rate). The pre-tightening force and friction force generated by the elastic deformation of the material make the outer 3K carbon fiber tube closely fit the internal structure to form a "3K carbon fiber tube / polyimide aerogel" composite sandwich cylindrical structure without additional bonding or mechanical fixation, ensuring the overall mechanical properties and stability.

[0094] Finally, it should be pointed out that the above examples are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced equivalently without departing from the purpose and scope of the present application, and they should be covered in the scope of the claims of the present application.

Claims

1. A method for preparing a nanoporous polyimide aerogel sandwich cylindrical structure, characterized in that, Includes the following steps: S1, construct a mold, the mold comprising an inner cylindrical shell and an outer cylindrical shell arranged coaxially, and having an annular gap between the inner and outer layers; S2, prepare a polyamic acid precursor solution and chemically imidize it; S3, inject the uncured polyamic acid precursor solution after chemical imidization into the annular gap between the inner and outer layers of the mold, wait for it to cure to form a gel core layer, and use the shrinkage force during the gel curing process to make the gel core layer and the inner cylindrical shell maintain a preliminary pre-tight bond to form a bond, but separate from the outer cylindrical shell. S4. The composite obtained in step S3 is immersed in ethanol for solvent replacement, so as to enhance the pre-tightening force between the wet gel and the inner cylindrical shell again by means of the shrinkage force during the solvent replacement process. S5, supercritical drying is performed on the composite material after step S4, so that the gel core layer and the inner cylindrical shell are further tightly bonded by the gel shrinkage deformation caused by supercritical drying. S6, an outer cylindrical retaining sleeve is set on the gel core layer based on an interference fit to form a nanoporous polyimide aerogel sandwich cylindrical structure.

2. The preparation method according to claim 1, characterized in that, The polyamic acid precursor solution is prepared from solid polyamic acid and a solvent capable of dissolving polyamic acid.

3. The preparation method according to claim 1, characterized in that, The polyamic acid solution is prepared by polymerization of dianhydride monomer and diamine monomer; The dianhydride monomer is selected from one or more of pyromellitic dianhydride, biphenyl dianhydride, benzophenone tetracarboxylic dianhydride, and diphenyl ether tetracarboxylic dianhydride. The diamine monomer is selected from one or more of diaminodiphenyl ether, 4,4'-diphenyl ether diamine, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(4-aminophenyl)-5-aminobenzimidazole, m-phenylenediamine and 4,4'-diaminobenzoylaniline.

4. The preparation method according to claim 1, characterized in that, The inner cylindrical shell is made of the structural target surface material, and the outer cylindrical shell is made of a material whose surface chemical properties are inactive.

5. The preparation method according to claim 4, characterized in that, The inner cylindrical shell is constructed of metal or composite metal tube or carbon fiber tube; the outer cylindrical shell is made of at least one of the following materials: glass, polypropylene, polytetrafluoroethylene, epoxy resin.

6. The preparation method according to claim 1, characterized in that, In step S4, the conjugate is immersed in ethanol at room temperature, and the ethanol is replaced every 10-14 hours to allow for a soaking time of not less than 48 hours.

7. The preparation method according to claim 1, characterized in that, In step S5, the complex treated in step S4 is subjected to supercritical drying in a supercritical drying vessel. The pressure in the drying vessel is maintained at 8-12 MPa, the temperature is set at 30-50℃, and carbon dioxide is used to rinse the supercritical drying vessel to remove the liquid in the gel pores, thereby completing the supercritical drying.

8. The preparation method according to claim 1, characterized in that, In step S6, the inner diameter of the outer cylindrical retaining sleeve is determined based on the outer diameter and linear shrinkage rate of the gel sandwich layer before supercritical drying, and its inner diameter is equal to or less than the outer diameter of the gel sandwich layer after drying, so that the outer cylindrical retaining sleeve and the gel sandwich layer form an interference fit.

9. The preparation method according to claim 8, characterized in that, The linear shrinkage rate is set as the ratio of the difference between the outer diameter of the gel sandwich layer before drying and the outer diameter after drying to the outer diameter before drying.

10. A nanoporous polyimide aerogel sandwich cylindrical structure, characterized in that, It is prepared by any one of claims 1-9; the nanoporous polyimide aerogel sandwich cylindrical structure includes an inner cylindrical shell, a gel sandwich layer tightly attached to the outside of the inner cylindrical shell, and an outer cylindrical retaining sleeve interference-fitted to the outside of the gel sandwich layer.